A comparison of two methods of medical discharge summary generation. - van Walraven, Carl G. (University of Ottawa (Canada), 1998)
Background. The discharge summary is an important method of communicating information necessary for continuing patient care. Deficiencies in discharge summary content, accuracy, and timeliness are a common problem. To improve summaries, studies have assessed physician-in-training (housestaff) education, alteration of the summary format; and collating information within computer databases into a summary. The most promising technology for improving discharge summaries is the clinical database. Primary objective. To compare medical discharge summaries generated from a clinical database with those created by narrative letter dictation. Design. Randomized controlled trial assigning patients to database (DB) or dictated (dictated-random or D-R) summaries. This was preceded by a prospective cohort study where summaries for all patients were created by dictation (dictated-cohort or D-C group). Inclusion criteria and study setting. All patients admitted to and discharged alive from the general internal medicine service in a tertiary care teaching hospital. Intervention. For patients randomized to the DB group, housestaff completed forms capturing hospital and discharge information important for the discharge summary. This information was entered into a database along with portions of the admission history and physical-examination form. Information in the database was collated into a report to create a database discharge summary. For patients in the D-R and the D-C group, housestaff used narrative dictation to create summaries. (Abstract shortened by UMI.)
Keywords: Health Sciences, Medicine and Surgery.